ANALYSIS OF THE DETERMINANTS OF CRIME IN JAMBI PROVINCE - Ahmad Soleh; Yunie Rahayu; Sedat Balikaya; Abdul Wahid; Prima Audia Daniel; Aguston Kurniawan (Jurnal Development, 2025)
A person's limitations to meet daily needs caused by the lack of resources they have make some people commit unlawful acts because the purpose of this research is to find out and analyze the relationship and influence of Economic Growth, Unemployment, and Education on Criminals in Jambi Province in the 2013-2022 period. This study uses the Quantitative Correlation and Descriptive Analysis method. The Correlation Analysis Method was used to measure how much the relationship between each variable, namely Economic Care, Unemployment, Education and Criminalization in Jambi Province for the period 2013-2022. And the quantitative descriptive analysis method was used to measure how much influence the variables of economic growth, unemployment, education and crime in Jambi Province in the 2013-2022 period. The results of the study show that the Correlation Test of Economic Growth (X1) with Crime (Y) is 0.778 where the correlation number This means that Economic Growth has a relationship with Crime in the Strong closeness category. Unemployment (X2) with Crime (Y) is 0.799 where r = 79.9 % correlation figure This means a category of strong closeness. education (X3) with Crime (Y) of 0.692 where r = 69.2 % correlation rate This means that education has a relationship with crime in Jambi Province of the strong closeness category From the research conducted using a quantitative test which shows the results of regression analysis that the economic growth variable (X1) has a coefficient of -0.021 with a significance value of 0.026, which means that there is a negative and significant relationship between economic growth and the level of Crime.